A Mediated Moderation Model: Personality, Team Psychological Safety and Team Performance - Budianto, Tarman (Management Analysis Journal, 2021)
Team performance as the foundation of organization in dealing with the complexity of the work and increasing the its competitiveness. Literature have shown that team psychological safety is an important predictor of team performance. This study use Trait Activation Theory to develop and present a model that aims to find the interaction between personality, team psychological safety and team performance. Regarding personality framework, this study uses the perspective of The Five-Factor Model. The results suggest that: First, the indirect effects of Conscientiousness personality on team performance will be stronger in (a) work that requires freedom and (b) work with high attention/detail requirements. Second, the indirect effects of extraversion personality on Team performance will be stronger in (a) jobs that require high social skills, (b) jobs with a high level of competition requirements, and (c) work where someone must often deal with unpleasant responses. Third, the indirect effect of openness personality on team performance will be stronger in (a) work that requires freedom and (b) work with high requirements of creativity.